ZIARAH KUBUR DALAM PERSPEKTIF BUDAYA DAN AGAMA - Ismawati Ismawati (At-Taqaddum, 2012)
Javanese culture is gradually changing because culture is a mixture of Indian culture, Arab, and European (Dutch). This change occurs because the merchant marine from the qudside is coming to southeast Asia by taking long sea voyages. Javanese people identify their region as the land below the wind to distinguish it from the outside world of people who come from the west (India, Arab, and European) that country is on the wind.Transitional Islamic culture which was originally centered in the northern coastal urban areas fell into the hands of Sultan Agung, the ruler of the countryside. The Javanese coastal initially confirming the character of orthodox Islam as an international trade network is now following the Islamic character of the agrarian and rural society static whit pre-islamic influences.One result of acculturation between islam and local tradition is the birth of the devolutional visit to the grave ‘s tradition. The practice of many integrating between the religious values and cultural values, so it is not uncommon causing a debate in the Islamic religion it self.